Rekayasa, Takhta dan Malapetaka: Sebuah Pedoman - Kuswantoro; Masduki Asbari (Jurnal Pendidikan Transformatif, 2022)
The purpose of this research is to find out Gita Wirjawan's views from Gita Wirjawan's youtube channel entitled "Engineering, Throne, and Doom | Endgame The Shelf #2". In this study, researchers used descriptive qualitative research methods by observing notes based on data obtained through oral narration in a video show. The results of this study explain Gita Wirjawan's perspective on the 5 books he has read including Hacking Darwin by Jamie Metzel, Guns, Germs, and Steel by Jared Diamond, Doom by Niall Ferguson, The Next 100 Years: A Forecast for the 21st Century by George Friedman and Military Politics, Islam and the State in Indonesia: From Turbulent Transition to Democratic Consolidation by Marcus Mietzner.